2019
DOI: 10.21608/ejar.2019.68569
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Damage and Control in Wheat Growing Stages, Sohag Governorate, Egypt

Abstract: odent survey and damage of wheat tillers were done, at different growing stages, in three locations within Sohag Governorate, Egypt. The Norway rat, Rattus norvegicus, was the common species with 434 individuals, followed by Rattus rattus, with showing 348 individuals, while the Arvicunthus niloticus was 138 individuals. Maximum damage was recorded at wheat maturity stage. Three formulations of zinc phosphide 0.5% (A-zinc phosphide, B-zinc phosphide mixed with peanut butter and C-zinc phosphide mixed with egg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…These results are supported by those obtained bySoliman et al (2017),Desoky and Baghdadi (2019) in Sohag governorate andBaghdadi (2006) and Abd El-Galil (2019) in Assiut governorate, who found that R. r. frugivorus was the most presented species. While results differ from thoseAhmed et al (2019) in Sohag governorate, Egypt.…”
contrasting
confidence: 90%
“…These results are supported by those obtained bySoliman et al (2017),Desoky and Baghdadi (2019) in Sohag governorate andBaghdadi (2006) and Abd El-Galil (2019) in Assiut governorate, who found that R. r. frugivorus was the most presented species. While results differ from thoseAhmed et al (2019) in Sohag governorate, Egypt.…”
contrasting
confidence: 90%